Peran Religiusitas terhadap Quarter-Life Crisis (QLC) pada Mahasiswa - Alfiesyahrianta Habibie; Nandy Agustin Syakarofath; Zainul Anwar (Faculty of Psychology, Universitas Gadjah Mada, 2019)
The purpose of this study was to determine the role of religiosity in the quarter-life crisis in students. The hypothesis proposed was that religiosity plays a role in the quarter-life crisis of students. This research used survey quantitative research methods. Participants in this study were 219 college students (95 males and 124 females) from various study programs in Indonesia aged 18-25 year old. The instruments used were the Abrahamic religiosity scale and the quarter-life crisis scale. Data were analyzed using regression analysis (p = 0.006; r = 0.034). Religiosity was found to predict how the student's facing a period of a quarter-life crisis and full of challenges to face.